Salt. Issue 4 (December 2021) - Unknown
Abstract : Turning, and turning around, on the Rann does not alter the white horizon. Salt—brilliant under the sun—dazzles the eyes, opens the lachrymal canals. We taste our own salinity as time seasons us.